Crack propagation law of rock with single fissure based on PFC2D - Yuan, Hao; Xiao, Taoli; She, Haicheng; Huang, Mei (Frontiers in Earth Science, 2023)
In the study of pre-fabricated single-fissured rock, the failure mode, mechanical properties and propagation law of rock are affected by the length and inclination angle of fissure. In this study, artificially prepared marble-like rocks with different fissure characteristics were used as rock representatives, using PFC2D software to establish a uniaxial compression model tests for rocks with fissures. The effects of different fissure lengths and inclination angles on the failure mode and crack initiation and propagation of rock-like structures were systematically studied. The results show that: (1) The failure mode of the rock with a single fissure under different lengths and inclination angles of the fissure was analyzed in detail, revealing the influencing factors and deep-seated mechanisms of destroyed rock. (2) According to the PFC2D simulation results, it was found that the variation law of characteristic variables changes with the inclination angle and length of the fissure and the internal relationship between the variables. (3) The variation in crack initiation and propagation characteristics with the inclination angle and length of the prefabricated fissure was simulated using PFC2D, revealing the mechanism of macroscopic mechanical behavior of rocks containing single fissures in the process of crack initiation, propagation, and failure at the micro-level.